A Computerized Method for Delay Risk Assessment Based on Fuzzy Set Theory using MS Project™ - Budayan, Cenk; Dikmen, Irem; Birgonul, M. Talat; Ghaziani, Aydin (KOREAN SOCIETY OF CIVIL ENGINEERS-KSCE, 2018)
In this paper, we present a computerized method as an add-in to MS Project (TM) for risk identification and estimation of delay. A delay analysis ontology is incorporated so that the users can identify causes of delay at the activity level and assess frequency and impact of risks using their previous experience, expertise and judgement. Testing and validation findings demonstrate that the software is easy to use and gives reliable results. Decision-makers can use this software during risk identification and planning phases to incorporate their judgment about potential risk sources that may lead to project delay. The outputs of the software make it easy for decision-makers to understand the level of delay risk at the activity level, explore how criticality of activities may change under different risk occurrence scenarios and estimate amount of delay. By utilizing the software, effective risk response and allocation strategies may be formulated to mitigate the delay risk and communicate delay risk information between various project participants.
Keywords: scheduling; delay analysis; delay assessment; fuzzy set; CONSTRUCTION PROJECTS; LOGIC APPROACH; INDEX; Engineering